APPLICATION OF MARKOV PROCESSES AS EFFICIENT INSTRUMENT FOR MAN-AGEMENT DECISION MAKING ON THE BASIS OF ENTERPRISE BUSINESS MODEL-ING - Evgeniya R. Khabibullina (Advanced Engineering Research, 2012)
The issues concerning the potential application of Markov processes theory for efficient management decision making based on the production enterprise business modeling are considered.